Trouble shooting. (Economist, 2015)
The article discusses American cyber-security in relation to Chinese hackers and computer- and network-related hacking attacks on U.S. computers and networks as of 2015. According to the article, the American government led by U.S. President Barack Obama will likely initiate economic sanctions against the Chinese companies that have likely profited from the theft of U.S. corporate trade secrets. Chinese President Xi Jinping's plan to visit Obama in Washington, D.C. is also examined.